Metsamor: report after the 2019 season - Krzysztof Jakubiak (Polish Archaeology in the Mediterranean, 2020)
The 2019 season in Metsamor confirmed the functioning of the settlement in the Urartian period. House II, discovered during the fieldwork, is the first architectural structure built at the beginning of the Early Iron Age period which, after some possible rearrangements, retained control over the Aras valley during the Urartian kingdom. Pottery discovered there confirms that the already excavated part of the settlement was extensively used after the fall of Urartu. A pit grave dated to the 7th century BC yielded a late Urartian cylinder seal.